Haemodynamic effects of central neural blocks - Borodičienė, Jurgita; Gudaitytė, Jūratė (Acta medica Lituanica, 2012)
Haemodynamic effects are the most important physiological responses to central neural blocks. This article is focused on the etiology of hypotension, bradycardia and asystole understanding of which is essential for the anesthesiologist for successful management in the perioperative period. The main causes of cardiovascular changes are decreased cardiac output, systemic vascular resistance and reflexes related to baroreceptors. Hypotension and / or bradycardia are usually of short duration and easily treatable. However, haemodynamic changes in hypovolaemic, elderly patients with comorbidity, and patients with increased catecholamine production, due to excessive alcohol intake, emergency situation, can be significant with worse outcomes. Therefore it is essential to correct hypovolaemia before surgery. Timely notification, identification and appropriate treatment of haemodynamic changes caused by already performed central neural blockade remain important in the perioperative period as well. Vital functions must be monitored throughout surgery so that adverse cardiovascular reactions could be managed with timely and adequate treatment including elevation of the legs, oxygen and infusion therapy, vasoactive and anticholinergic drugs.
Keywords: haemodynamic effects; central neural blocks; spinal anaesthesia; epidural anaesthesia